2013
DOI: 10.4187/respcare.02225
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Admission Pattern on the Outcome of Patients Admitted to a Respiratory Intensive Care Unit: Does a Step-Down Admission Differ From a Step-Up One?

Abstract: BACKGROUND:The outcomes of patients admitted to a respiratory ICU (RICU) have been evaluated in the past, but no study has considered the influence of location prior to RICU admission. METHODS: We analyzed prospectively collected data from 326 consecutive patients admitted to a 7-bed RICU. The primary end points were survival and severity of morbidity-related complications, evaluated according to the patient's location prior to RICU admission. Three admission pathways were considered: step-down for patients tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 31 publications
0
19
0
1
Order By: Relevance
“…21 It may be classified as follows: step-down pathway, which corresponds to an admission from an ICU; step-up pathway, which corresponds to an admission from a hospital ward; or direct pathway, which corresponds to an admission from the emergency department. 22 These patterns differed in our hospital according to the pre-RICU period or RICU period in that the 3 previously described patterns were possible during the pre-RICU period, whereas the step-down pattern was the one authorized by the Regional Health Agency. Patients admitted in a RICU according to a step-up pattern usually have a poorer prognosis than those admitted according to the step-down pattern.…”
Section: Discussionmentioning
confidence: 75%
“…21 It may be classified as follows: step-down pathway, which corresponds to an admission from an ICU; step-up pathway, which corresponds to an admission from a hospital ward; or direct pathway, which corresponds to an admission from the emergency department. 22 These patterns differed in our hospital according to the pre-RICU period or RICU period in that the 3 previously described patterns were possible during the pre-RICU period, whereas the step-down pattern was the one authorized by the Regional Health Agency. Patients admitted in a RICU according to a step-up pattern usually have a poorer prognosis than those admitted according to the step-down pattern.…”
Section: Discussionmentioning
confidence: 75%
“…Patients who may worsen and need ICU care will be better served in an ICU than patients awaiting ICU downgrade [36]. …”
Section: Methodsmentioning
confidence: 99%
“…factor in RHDUs, accounting for 36% of the causes of death in severe acute respiratory failure (ARF) [15]. In the clinical setting of a tremendously increasing burden of critically ill respiratory patients, RHDUs provide a specialised quality of care for ARF patients who require an intermediate level of care between ICU and wards, with health resources optimisation in Europe [16].…”
mentioning
confidence: 99%
“…A recent Spanish multicentre study [29] demonstrated that although the incidence of sepsis/septic shock remained unchanged during a 10-year period, implementation of SSC guidelines decreased the severity of illness and overall mortality. Mortality of sepsis has been shown to be correlated with pre-ICU/RHDCU admission site [13,15]. Patients with sepsis/septic shock identified in emergency departments, general wards and ICUs in Europe were more severely ill than those in the USA with similar mortality if adjusted for severity of illness and organ dysfunction.…”
mentioning
confidence: 99%
See 1 more Smart Citation